(untitled) (Journal of Student Affairs in Africa, 2021)
Traditional advising responsibilities are shifting to include a holistic, learning-based and developmental approach that favours advising of the entire university experience. A dearth of systematic empirical evidence exists on advisors’ perceptions of the value of advising students during the COVID-19 pandemic in the South African context. The purpose of this study is to elucidate advisors’ perceptions of the complexity and challenges inherent in their responsibilities during the pandemic. This case study draws on a qualitative research design; it is based on semi-structured in-depth interviews undertaken with nine advisors in 2020. The central research questions posed in this study are: how do advisors describe their perceptions of their responsibilities within the COVID-19 pandemic, and how might these contribute to future practices? The findings indicate that advising during the pandemic has transcended the typical transactional dissemination of information to include addressing contextual environmental and resource challenges, social justice imperatives, emergency remote learning, asynchronous advising challenges and data-informed advising. These responsibilities have encompassed a holistic approach to advising and to getting to know students as ‘whole people’. Adjustments and transitions to emergency remote learning have highlighted social inequalities in access to data, to internet and electricity connectivity, which have served as impediments to students’ learning, and to educational experiences. Some home environments were not conducive to studying but necessitated doing household chores and herding cattle. The findings also indicate that an institution’s advising delivery model should enhance advisors’ abilities to perform their responsibilities. A network of cascaded responsibilities that incorporates greater involvement of lecturers in advising could contribute to a shared responsibility between lecturers and central, faculty and peer advisors. Insights gained may lead to a more nuanced understanding of advisors’ responsibilities as they relate to student learning and to the overall educational experience to promote retention and student success in a post-pandemic era.